2019
DOI: 10.1002/jcb.29049
|View full text |Cite
|
Sign up to set email alerts
|

Integrative prognostic subtype discovery in high‐grade serous ovarian cancer

Abstract: Objective We sought to identify novel molecular subtypes of high‐grade serous ovarian cancer (HGSC) by the integration of gene expression and proteomics data and to find the underlying biological characteristics of ovarian cancer to improve the clinical outcome. Methods The iCluster method was utilized to analysis 131 common HGSC samples between TCGA and Clinical Proteomic Tumor Analysis Consortium databases. Kaplan‐Meier survival curves were used to estimate the overall survival of patients, and the differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…25 mRNA profiling using the TCGA data set found that upregulated DSG2 expression correlated with worse highgrade serous ovarian cancer (HGSC) prognosis among platinum-sensitive patients. 26 Chen et al correlated DSG2 expression and survival of ovarian cancer patients and concluded that DSG2 may be involved in the progression of specific types of ovarian cancer. 27 Here we specifically investigated DSG2, including shed serum DSG2, as a potential ovarian cancer biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…25 mRNA profiling using the TCGA data set found that upregulated DSG2 expression correlated with worse highgrade serous ovarian cancer (HGSC) prognosis among platinum-sensitive patients. 26 Chen et al correlated DSG2 expression and survival of ovarian cancer patients and concluded that DSG2 may be involved in the progression of specific types of ovarian cancer. 27 Here we specifically investigated DSG2, including shed serum DSG2, as a potential ovarian cancer biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…(B) The Kaplan-Meier Plotters demonstrated the different overall survival of TPX2 highly expressed LUAD patients (red) and TPX2 lowly expressed LUAD patients (black) in TCGA, GSE30219, GSE42127, GSE50081, GSE68465, and GSE72094 datasets systems based on the transcriptional profiling of cancers are developed. Self-organizing maps (SOMs) clustering, 52,53 integrative iCluster clustering, 5,54,55 networkbased consensus molecular classification (CMS), 56,57 and nonnegative matrix factorization (NMF) clustering 26,28,31,34 are all proved to be robust cancer classification systems. However, for the same cohort of tumor patients, distinct clustering methods may result different classification.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to beforementioned works, there are a huge examples of iCluster use with TCGA. For instance, in Xie et al (2019) an integrative analysis was carried out with iCluster through RNAseq and proteomics data to analyse the OV subtype. The results showed two clusters with different survival rates; the method identified 18 mRNAs and 38 proteins as distinct molecules among subtypes.…”
Section: Machine Learning As a Source Of New Knowledgementioning
confidence: 99%